Grapho-Barbarisms in the Headlines of Ukrainian Media Texts - Navalna, Maryna; Kostusiak, Nataliia; Mezhov, Oleksandr; Marchuk, Liudmyla; Buhaiova, Oksana; Novoseletska, Svitlana; Shapran, Nataliia; Khomych, Tetiana; Musiichuk, Tetiana; Bobkov, Vadym (My University, 2024)
The article analyzes the most used graphic barbarisms (grapho-barbarisms) in the headlines of the most widely circulated Ukrainian mass media. In accordance with the goal, the functional features of grapho-barbarisms in the language of modern mass media were investigated, their potential and stylistic role were clarified. Achieving the set goal required solving the following tasks: 1) to establish relevant non-linguistic factors affecting the actualization of grapho-barbarisms; 2) to interpret different types of words and phrases written in Latin, to highlight the topics of publications where they are used; 3) to determine the expediency/inexpediency of using grapho-barbarisms in the language of mass media, to characterize them in the context of language adaptation and in comparison with Cyrillic variants. According to the results of the research, it was established that graphic barbarisms form the largest thematic groups, which denote types of weapons and military equipment, various support tools, foundations, charitable institutions, volunteer organizations, subjects and concepts of the field of information technologies, names of sources of information, magazines, publishers, sites, etc. It was concluded that graphic barbarism prevails in the headlines of news genres. It has been observed that sometimes journalists use Cyrillic versions, but this phenomenon is fragmentary. Borrowings reproduced in the Latin alphabet complicate the perception of messages by information consumers and litter the Ukrainian literary language. The source base of the research consisted of the headline complexes, which contained words and phrases written in Latin, mainly collected from the Ukrainian media in 2024.
Keywords: vocabulary; borrowings; barbarisms; grapho-barbarisms; anglicisms; foreign language inclusions; abbreviations; extralinguistic factors; stylistic role